A biphasic tumor consisting of pilocytic astrocytoma with an anaplastic solitary fibrous tumor component in the pineal region: A case report and literature review. Issue 3 (17th September 2012) - Jang, Seon Jung; Kim, Jinna; Cho, Jin Mo; Noh, SongMi; Park, Sung‐Hye; Kim, Se Hoon
Abstract : Here we report a case of a biphasic tumor consisting of pilocytic astrocytoma with anaplastic solitary fibrous tumor component in the pineal region. The majority of the tumor showed typical histologic features of pilocytic astrocytoma. A minor part of the tumor showed marked proliferation of short spindle cells around vessels. These spindle cells showed CD34 and CD99 immunoreactivity. From a review of the literature, we found that only one similar case has been reported. Contrary to the reported case, our case showed anaplastic features of solitary fibrous tumor histology.